Theorist, Composer, Music Teacher Mikhail Berezovsky and His “Adaptation” of Nikolay Diletsky’s Treatise - Anna V. Bulycheva; Aleksandra V. Alexandrina (Современные проблемы музыкознания)
The article is devoted to the Baroque theorist and composer Mikhail Berezovsky. In the scholarly literature, it is already possible to find some references to his musicological treatise consisting of two parts: A Brief Exposition of Musical Singing (elementary music theory) and Grammar. A Collection from Many (theory of composition). We have also discovered Berezovsky’s 12-voice partesny concerto Who shall ascend the Hill of the Lord? Due to filigree research as well as indirect data, the dates of the composition of both works have been established as pertaining to the 1730s. Both of the survived copies of Grammar. A Collection from Many are placed in theoretical manuscripts adjacent to Nikolay Diletsky’s The Grammar of Musical Singing. The comparative analysis of the two Grammars shows, that Berezovsky’s treatise appears to be a concise presentation of Diletsky’s ideas, slightly updated with new information. The same pertains to the terminology of the: it is freed from an excessive amount of Latin synonyms and supplemented by new terms not yet relevant during the time of Diletsky. All the musical examples are newly composed by Berezovsky, and none of them is derived from Diletsky. The comparison of the musical examples with the music of the concerto Who shall ascend into the hill of the Lord? Has made it possible for us to identify a number of correspondences, albeit, not literal ones. The complete text of both parts of Berezovsky’s treatise supplements the article, having been adapted to contemporary Russian, as does a dictionary of terminology. The abridged revised version of Nikolay Diletsky’s The Grammar of Musical Singing, originally written in 1670s, made in 1730s for a new generation of new readers, could be appreciated only as an evidence of a stagnation that occurred in the Russian partesny singing theory. The musical style changed considerably; at the same time, the music theory was progressing at a much more slow pace.